PENGARUH NONPERFORMING LOAN DAN LIKUIDITAS PADA PENYALURAN KREDIT DAN PROFITABILITAS BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Jaya, I Made Gaura Hari; Suardana, Ketut Alit (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine how the influence of non-performing loans and liquidity on lending and profitability at the Rural Bank of Badung Regency. The population in this study were all Badung Regency Rural Banks registered with the Financial Services Authority in 2018-2020. The sampling method used was purposive sampling and obtained a sample of 138 samples. The data analysis technique used in this research is Path Analysis. The results show that non-performing loans have a negative effect on lending and profitability, liquidity has a positive effect on lending and profitability, credit distribution has a positive effect on profitability, credit distribution mediates the effect of non-performing loans on profitability, while lending does not mediate the effect of liquidity on profitability at the Rural Banks in Badung Regency